'I was altogether out of tune with my colleagues': Conor Cruise O'Brien and Northern Ireland, 1969–77. Issue 167 (May 2021) - Kelly, Stephen
Abstract: This article critically re-assesses Conor Cruise O'Brien's attitude to Northern Ireland between 1969 and 1977. It argues that O'Brien's most significant contribution to public life was the ability to deconstruct many aspects of Irish nationalism, specifically his rejection of the Irish state's irredentist claim over Northern Ireland. In doing so, it contends that O'Brien was one of the most important, and outspoken, champions of so-called 'revisionist nationalism' of his generation. The article examines three themes in relation to O'Brien's attitude to Northern Ireland: his attack on the Irish state's anti-partitionism; his rejection of Irish republican terrorism; and his support for the 'principle of consent' argument. The article illustrates that O'Brien was criticised in nationalist circles and accused of committing political heresy. Indeed, his willingness to challenge the attitude of most mainstream Irish politicians on Northern Ireland invariably left him an isolated figure, even among his own Labour Party comrades. Writing in his Memoir, O'Brien neatly summed up the difficult position in which he found himself: 'I was altogether out of tune with my colleagues over Northern Ireland'.